Uptake and translocation of nitrogen in patumma (Curcuma alismatifolia) by leaves or root - Anuwong C. (2017)
© 2017 Taylor & Francis Group, LLC. An adequate supply of nitrogen (N) is important for patumma growth and flower quality. This study aimed to compare the uptake and translocation of N by foliar and root application. Fertilization with 15 nitrate (NO 3 )-N via roots or leaves was carried out at four stages, at the 1st to 4th fully expanded leaf (FEL) stages, and the plants were sampled at each successive stage. The uptake and translocation of 15 N from foliar or root applications showed relatively similar patterns at all stages. Although the N fertilizer utilization rate by roots was higher than that via leaves, the foliar application stimulated reproductive growth by earlier flowering. The N supplied at the 1st FEL and the 2nd FEL was utilized mainly in leaves, whereas supplying N at the 3rd and 4th FEL promoted flower quality. Fertilizer application method and stage of application influence the utilization rate and translocation of N to the sink organs.